The impact of annealing temperatures and chemical assays on the mechanical properties and electrical conductivity of CuNi9Sn2 - Ivanović Aleksandra; Dimitrijević Silvana; Dimitrijević Stevan; Mir Shaila (Mining and Metallurgy Engineering Bor)
The interest in copper-based alloys with nickel and tin is constantly increasing. In this regard, certain tests were performed on CuNi9Sn2 alloy samples. In this work, the influence of annealing temperature and chemical composition on the mechanical properties and electrical conductivity of CuNi9Sn2 was investigated. Tensile strength (Rm), yield strength (Rp0,2) and elongation (A) were determined in the function of annealing temperatures and content of added elements (Li and B) at a constant deformation degree.